2019
DOI: 10.1038/s41598-019-51870-x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of bacteria associated with western corn rootworm life stages reveals no difference between insects reared in different soils

Abstract: Western corn rootworm (Diabrotica virgifera virgifera LeConte) is a serious pest of maize (Zea mays L.) in North America and parts of Europe. With most of its life cycle spent in the soil feeding on maize root tissues, this insect is likely to encounter and interact with a wide range of soil and rhizosphere microbes. Our knowledge of the role of microbes in pest management and plant health remains woefully incomplete, yet that knowledge could play an important role in effective pest management strategies. For … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Selection for Bt resistance could potentially favour bacteria known to degrade Cry proteins or alter the gut environment (i.e., biofilms, antimicrobials) to reduce binding or competitively exclude harmful bacteria (Patil et al, 2013;Shan et al, 2014;Vásquez et al, 2012). In addition, the harbouring of nutrient-providing or plantdigesting bacteria could increase tolerance to Bt as nutritional differences in diet correlate to alterations in Bt susceptibility (Deans et al, 2017;Ludwick et al, 2018). Previous experiments involving combinations of bacterial spray formulations, spores and purified crystals, following antibiotic treatment on artificial diet have yielded conflicting results Raymond et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Selection for Bt resistance could potentially favour bacteria known to degrade Cry proteins or alter the gut environment (i.e., biofilms, antimicrobials) to reduce binding or competitively exclude harmful bacteria (Patil et al, 2013;Shan et al, 2014;Vásquez et al, 2012). In addition, the harbouring of nutrient-providing or plantdigesting bacteria could increase tolerance to Bt as nutritional differences in diet correlate to alterations in Bt susceptibility (Deans et al, 2017;Ludwick et al, 2018). Previous experiments involving combinations of bacterial spray formulations, spores and purified crystals, following antibiotic treatment on artificial diet have yielded conflicting results Raymond et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Douglas [170] theorized the exploitation of insect microbiomes could provide new pest management techniques. Studies have shown the western corn rootworm actively selects for microorganisms it harbors [171,172]. Larvae reared in two different soils harbor similar bacterial communities even though the soil samples vary widely in community composition [172].…”
Section: Using Soil Microbials To Disrupt Wcr Gut Microbiomementioning
confidence: 99%
“…Studies have shown the western corn rootworm actively selects for microorganisms it harbors [171,172]. Larvae reared in two different soils harbor similar bacterial communities even though the soil samples vary widely in community composition [172]. The WCR bacterial community commonly consists of species of Serratia, Pseudomonas, Klebsiella, Acinetobactor, Streptomyces, and Tsukamurella, with other species appearing in high abundance but sporadically [171][172][173][174].…”
Section: Using Soil Microbials To Disrupt Wcr Gut Microbiomementioning
confidence: 99%
See 2 more Smart Citations